(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2021)
In manga translation, when original image and written representations are regarded as inappropriate content to the target readers’ socio-cultural context, censorship is imposed. Nevertheless, research on censorship in manga translation in Malaysia has not been given due attention. Previous studies show that self-censorship influences translation, but it is not examined within the scope of manga translation. As such, the objective of this study is to examine the censorship practices in manga translation in Malaysia. This study adopts a qualitative content analysis approach to analyse six Malay translations and their respective source texts based on the publishing guideline of the Printing Presses and Publications Act 1984 [Act 301] and translation procedures proposed by Klaus Kaindl. The analysis shows that the censorship practice in manga translation is a combination of institutional and self-censorship. In institutional censorship, the translation procedures of detraction, addition, substitution, deletion and couplets are used, while in self-censorship, the process is involves substitution, deletion and addition. The current study recommends the adoption of institutional censorship procedures as guidelines in handling sensitive representations and a review of the self-censorship procedures to ensure faithful translations.